KETERBACAAN TEKS BAHASA INDONESIA DAN MEMBACA PEMAHAMAN SISWA KELAS X SMK MUHAMMADIYAH 2 PEKANBARU - Efriliani, Efriliani; Auzar, Auzar; Razak, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is titled The Readability of Indonesian Text Book and Reading Comprehension Students of Class X SMK Muhammadiyah 2 Pekanbaru. This study aims to describe the relationship between the readability of Indonesian texts and reading the understanding of students of class X SMK Muhammadiyah 2 Pekanbaru. The data of this research is the result of Indonesian language readability test and reading comprehension ability of class X students of SMK Muhammadiyah 2 Pekanbaru consisting of 13 parallel classes with population 415 students and sample size 204 students. Technique of collecting data by giving test of Indonesian text readability and comprehension reading test. To find out whether or not the value expected by the students is calculated using chi square, to find out whether there are differences in mean groups between samples is calculated using Kruskall Wallis, and to find the relationship between the readability of Indonesian texts and reading comprehension is calculated using Rank Order correlation. Based on the research, it is found that (1) the readability of Indonesian text is moderate; (2) the readability of Indonesian texts between different sample groups, Meaning, there is a difference between the readability of Indonesian text between fellow class X or between one or more classes of X; (3) the reading comprehension ability is low; (4) the ability to read understanding among groups of the same group. Meaning, there is no difference reading comprehension between fellow class X or between one or several classes of X; (5) the readability of Indonesian texts and reading comprehension have no significant relationship, Meaning, there is no relation of readability of text and reading comprehension. It can be concluded that the relationship between the two only reached the correlation coefficient of 0.353 including the qualification of low relations.Key Words: readability, text, reading comprehension, cloze test